2015
DOI: 10.4103/0973-029x.157223
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation by modified Demirjian′s method (2004) and its applicability in Tibetan young adults: A digital panoramic study

Abstract: Context:Estimation of the age is a procedure adopted by anthropologists, archeologists and forensic scientists. Different methods have been undertaken. However none of them meet the standards as Demirjian's method since 1973. Various researchers have applied this method, in both original and modified form (Chaillet and Demirjian in 2004) in different ethnic groups and the results obtained were not satisfactory.Aims:To determine the applicability and accuracy of modified Demirjian's method of dental age estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…A strong positive association was found between the chronological (real) age and the dental age. The results were in accordance with the literature [4,11,12]. An age estimation method can be considered efficient and effective if it has higher accuracy and precision with relatively low bias.…”
Section: Resultssupporting
confidence: 90%
“…A strong positive association was found between the chronological (real) age and the dental age. The results were in accordance with the literature [4,11,12]. An age estimation method can be considered efficient and effective if it has higher accuracy and precision with relatively low bias.…”
Section: Resultssupporting
confidence: 90%
“…One study found coincidence of scores between the original investigations and a study on schoolchildren in some Indian states. The Demirjian method was considered to underestimate the real age for girls and boys in Indian populations 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…One study found coincidence of scores between the original investigations and a study on schoolchildren in some Indian states. The Demirjian method was considered to underestimate the real age for girls and boys in Indian populations 32,33 . In Argentina, researchers from the University of Cuyo in Mendoza Province calculated dental ages in a population in the Cuyo region using Nolla and Demirjian methods, analyzing 374 panoramic scans of children and teenagers aged 5 to 17 years.…”
Section: Discussionmentioning
confidence: 99%
“…[1415] Forensic odontology plays an important role in establishing the sex of the victims with bodies mutilated beyond recognition due to major mass disasters.…”
Section: Discussionmentioning
confidence: 99%